The The analysis of Jean Baptiste Grenouille's desire in Patrick Suskind's perfume: The Story of Murderer - yusuf bakhtiar (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
Analyzing Jean Baptiste Grenouille through a Lacanian lens offers a compelling exploration of desire, identity, and the unconscious in